Consumption behavior in Islam - Yulianti, Yulianti; Maryati, Tatik (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
This paper describes one of the theories of Islamic microeconomics: Consumption Behavior in Islam which illustrates that the purpose of consumption in Islam is not merely seeking maximum satisfaction but aims for benefit (maslahah). This research is a qualitative research by conducting literature research because the study focused on library materials by tracing, reviewing and recording various literature in accordance with the subject matter of academic standards. This discussion is integrated syntactically, that is, it follows certain rules that can be connected logically or with others with the basic data observed. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.